Water-soluble film and method for producing same, and drug package and method for producing same

By using a modified polyvinyl alcohol-based resin to improve the compatibility of the Plulandosaccharide, a water-soluble film with excellent compatibility, water-soluble and mechanical properties was produced, which solved the problem of insufficient strength and tensile properties of the existing films in independent packaging applications, and achieved a stronger and better moldable film.

CN119816555APending Publication Date: 2025-04-11MITSUBISHI CHEM CORP

Patent Information

Application Number
CN202380063278.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-18
Filing Date
2023-11-17
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The incompatibility of the purulindosaccharide and polyvinyl alcohol resins is insufficient, resulting in poor physical properties and appearance of the film. Especially in independent packaging applications such as food and pharmaceuticals, the mechanical properties of the film are insufficient, such as strength and tensile properties.

Method used

A modified polyvinyl alcohol-based resin modified with hydrophilic groups was used to improve the compatibility between the prilandosaccharide and the polyvinyl alcohol-based resin, and a water-soluble film was produced through the casting process and the drying process.

Benefits of technology

It achieves excellent compatibility, water solubility, mechanical properties, excellent moldability and sealing properties of the film. It is suitable for independent packaging purposes, especially for independent packaging bodies of pharmaceuticals and foods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005293395220000221
    Figure BDA0005293395220000221
  • Figure BDA0005293395220000231
    Figure BDA0005293395220000231
Patent Text Reader

Abstract

Provided is a water-soluble film containing pullulan and a modified polyvinyl alcohol-based resin modified with a hydrophilic group, the water-soluble film having sufficiently high intermiscibility even if the pullulan and the polyvinyl alcohol-based resin are contained, having excellent water solubility and mechanical properties of the film, and being useful for packaging applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a water-soluble film containing pullulan, and more particularly to a water-soluble film containing pullulan and a polyvinyl alcohol-based resin, a drug package using the same, and methods for producing the same.

[0002] In recent years, from the perspective of protecting the global environment, there has been a demand for the development of a more biodegradable film using a natural raw material to replace the conventional plastic film containing a petroleum-derived raw material.

[0003] On the other hand, as shown in Patent Documents 1 and 2, water-soluble films using pullulan, a water-soluble polysaccharide, as a raw material of natural origin are known. For example, Patent Document 1 records that a water-soluble film containing pullulan and polyvinyl alcohol has excellent printability and adhesion. In addition, Patent Document 2 records that a film containing pullulan and a water-soluble polymer can be used for edible purposes.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 5-001198

[0007] Patent Document 2: Japanese Patent Application No. 2005-528328 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] However, pullulan sometimes has insufficient compatibility with other water-soluble polymers such as polyvinyl alcohol resins, and the water-soluble films of the above-mentioned patent documents 1 and 2 have poor physical properties and appearance of the obtained films, especially in the independent packaging applications of food, medicine, etc., which require excellent film formability, mechanical properties such as strength and stretchability are insufficient, and further improvement is required to form a tougher and excellently formable film. In addition, appearance is also valued in independent packaging applications, and therefore, further improvement is required.

[0010] Therefore, in this context, the present invention provides: a water-soluble film and a method for producing the same, and a pharmaceutical package and a method for producing the same, which have sufficiently high compatibility between pullulan and a polyvinyl alcohol-based resin, excellent water solubility, and excellent mechanical properties such as film strength and elongation and are useful for packaging applications.

[0011] Solutions for solving problems

[0012] Therefore, the present inventors conducted intensive studies in view of the above circumstances and found that a water-soluble film having excellent compatibility, water solubility, and mechanical properties of the film can be obtained by using a modified polyvinyl alcohol-based resin modified with a hydrophilic group as a polyvinyl alcohol-based resin used in combination with pullulan.

[0013] In addition, since the polyvinyl alcohol-based resin is a biodegradable resin, the above-mentioned problems can be solved without significantly reducing the biodegradability of the entire water-soluble film.

[0014] That is, the present invention has the following aspects.

[0015] [1] A water-soluble film comprising pullulan and a modified polyvinyl alcohol-based resin modified with a hydrophilic group.

[0016] [2] The water-soluble film according to [1], wherein the modified polyvinyl alcohol-based resin modified with a hydrophilic group is a polyvinyl alcohol-based resin modified with an anionic group.

[0017] [3] The water-soluble film according to [1] or [2], wherein the content ratio of the pullulan to the modified polyvinyl alcohol-based resin modified with a hydrophilic group is 1 / 99 to 99 / 1 in terms of mass ratio.

[0018] [4] The water-soluble film according to any one of [1] to [3], further comprising a plasticizer.

[0019] [5] The water-soluble film according to [4], characterized in that the content ratio of the pullulan to the modified polyvinyl alcohol resin modified with a hydrophilic group is 5 / 95 to 80 / 20 in terms of mass ratio, and the content of the plasticizer is 5 to 60 parts by mass relative to a total of 100 parts by mass of the pullulan and the modified polyvinyl alcohol resin modified with a hydrophilic group.

[0020] [6] The water-soluble film according to any one of [1] to [5], further comprising a filler.

[0021] [7] The water-soluble film according to [6], wherein the filler is starch.

[0022] [8] The water-soluble film according to [7], characterized in that the film contains 2 to 60 parts by mass of the starch per 100 parts by mass of the pullulan.

[0023] [9] The water-soluble film according to any one of [6] to [8], wherein the modified polyvinyl alcohol-based resin modified with a hydrophilic group is a polyvinyl alcohol-based resin modified with an anionic group,

[0024] The content ratio of the pullulan to the anionic group-modified polyvinyl alcohol-based resin is 5 / 95 to 80 / 20 in terms of mass ratio.

[0025]

[10] The water-soluble film according to any one of [1] to [9], wherein the water content is 3 to 15% by mass.

[0026]

[11] The water-soluble film according to any one of [1] to

[10] , which is used for drug packaging.

[0027]

[12] The water-soluble film according to any one of [1] to

[10] , which is used for food packaging.

[0028]

[13] A method for producing a water-soluble film as described in any one of [1] to

[12] , characterized in that it comprises the following steps: a casting step of preparing a film-forming raw material containing pullulan and a modified polyvinyl alcohol-based resin modified with a hydrophilic group, and casting the aforementioned film-forming raw material on a casting surface; and a drying step of drying the aforementioned film-forming raw material cast on the casting surface.

[0029]

[14] A medicine package, comprising: a package comprising the water-soluble film according to

[11] , and a medicine enclosed in the package.

[0030]

[15] The drug packaging body according to

[14] is characterized in that the drug is a liquid detergent.

[0031]

[16] A method for manufacturing a drug package according to

[14] or

[15] , characterized by comprising the following steps:

[0032] preparing a first water-soluble film, a second water-soluble film and a reagent;

[0033] The first water-soluble film and the second water-soluble film are placed opposite to each other, the medicine is arranged between the first water-soluble film and the second water-soluble film, the first water-soluble film and the second water-soluble film are overlapped, so that the first water-soluble film around the medicine abuts against the second water-soluble film, and the abutting portion is pressed.

[0034] Effects of the Invention

[0035] The water-soluble film of the present invention has excellent compatibility, water solubility, and mechanical properties of the film, and is also excellent in formability and sealing properties. Therefore, it is suitable for individual packaging purposes, and is particularly excellent as an individual package for medicines and foods. DETAILED DESCRIPTION

[0036] Hereinafter, the present invention will be described based on examples of the modes for carrying out the present invention. However, the present invention is not limited to the embodiments described below.

[0037] It should be noted that the term "film" in the present invention also includes "tape" and "sheet".

[0038] In the present invention, when expressed as "X to Y" (X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less" as well as "preferably greater than X" or "preferably less than Y".

[0039] Furthermore, when expressed as "X or more" (X is an arbitrary number) or "Y or less" (Y is an arbitrary number), it also includes the meaning of "preferably greater than X" or "preferably less than Y".

[0040] Hereinafter, the present invention will be described in detail.

[0041] The water-soluble film of the present invention refers to a film that dissolves in water at about room temperature (20° C.).

[0042] In the present invention, dissolution of the film is determined as follows.

[0043] That is, the film was cut into a size of 3 cm × 5 cm, placed in a 1-liter beaker filled with water (1 liter), fixed with a jig, and stirred with a stirrer (rotor length 3 cm, rotation speed 750 rpm) while maintaining the water temperature at 20°C. The situation in which no insoluble particles of the above-mentioned film with a diameter of more than 1 mm were observed was recorded as dissolved.

[0044] The water-soluble film of the present invention contains pullulan and a modified polyvinyl alcohol-based resin modified with a hydrophilic group. In addition, the drug package of the present invention includes: a package containing the water-soluble film and a drug encapsulated in the package. These are described below.

[0045] In addition, in the present invention, polyvinyl alcohol may be abbreviated as "PVA".

[0046] <<Water-soluble film>>

[0047] <Pullulan>

[0048] Pullulan is a type of polysaccharide composed only of glucose, and has a structure in which maltotriose formed by three glucose molecules linked by α1-4 bonds is linked by α1-6 bonds. It is usually obtained by culturing a microorganism (a type of filamentous fungus) in a culture medium containing molasses, is easily soluble in water, and has properties such as lubricity, adhesion, consolidation, adhesion, cohesion, film-coating, and formability.

[0049] In addition, there is also a modified pullulan in which a functional group is introduced to impart further properties.

[0050] The content of the above-mentioned pullulan is preferably 3% by mass or more of the water-soluble film, more preferably 4% by mass or more, further preferably 5% by mass or more, particularly preferably 8% by mass or more, and especially preferably 10% by mass or more. In addition, the upper limit is preferably 90% by mass or less, more preferably 80% by mass or less, further preferably 70% by mass or less, and particularly preferably 60% by mass or less. If the content of pullulan is within the above range, there is a tendency for the mechanical properties of the film, particularly the strength and transparency of the film to be excellent.

[0051] <Modified PVA-based resin modified with a hydrophilic group>

[0052] The modified PVA resin modified with a hydrophilic group used in the present invention (hereinafter, sometimes referred to as "hydrophilic group-modified PVA resin") preferably has an anionic group such as a carboxyl group, a sulfonic acid group, a phosphoric acid group, and at least one hydrophilic group selected from the group consisting of a pyrrolidone ring and an amino group. Among them, an anionic group is preferred, and a carboxyl group and a sulfonic acid group are particularly preferred. The above-mentioned hydrophilic group also includes salts of sodium, potassium, etc. of the above-mentioned functional groups.

[0053] Examples of the hydrophilic group-modified PVA resins include anionic group-modified PVA resins such as carboxyl-modified PVA resins, sulfonic acid-modified PVA resins, and phosphate-modified PVA resins, pyrrolidone ring-modified PVA resins, and amino-modified PVA resins.

[0054] [Anionic group-modified PVA resin]

[0055] The anionic group-modified PVA resin has an anionic group, and examples of the anionic group include a carboxyl group, a sulfonic acid group, a phosphoric acid group, etc. Among them, the anionic group is preferably a carboxyl group or a sulfonic acid group in terms of excellent solubility in water and chemical resistance.

[0056] The anionic group-modified PVA-based resin can be produced, for example, by saponifying a copolymer of a vinyl ester-based monomer and an anionic unsaturated monomer, or by post-modifying a PVA-based resin.

[0057] Examples of the unsaturated monomer having an anionic group include a carboxyl group-containing unsaturated monomer, a sulfonic acid group or sulfonate group-containing unsaturated monomer, and a phosphoric acid group-containing unsaturated monomer.

[0058] As the carboxyl group-containing unsaturated monomer, for example, there can be mentioned: carboxyl group-containing unsaturated compounds such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, and those whose carboxyl groups are neutralized in whole or in part by a base such as a basic compound (e.g., sodium hydroxide, potassium hydroxide, etc.), or monoalkyl esters of the above carboxyl group-containing unsaturated compounds such as methyl acrylate, ethyl acrylate, methyl methacrylate, monomethyl fumarate, monomethyl maleate, and dialkyl esters of the above carboxyl group-containing unsaturated compounds such as diethyl fumarate and diethyl maleate. The carbon number of these esters is usually 1 to 20 from the aspects of economy and practicality, and preferably 1 to 10, and particularly preferably 1 to 4.

[0059] Among these, maleic acid compounds are preferred, and monomethyl maleate is more preferred.

[0060] Examples of the unsaturated monomer containing a sulfonic acid group or a sulfonate group include olefin sulfonic acids or salts thereof such as vinyl sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid; sulfoalkyl maleates such as sodium sulfopropyl-2-ethylhexyl maleate, sodium sulfopropyl tridecyl maleate, and sodium sulfopropyl eicosyl maleate; sulfoalkyl (meth) acrylamides such as sodium sulfomethacrylamide, sodium sulfo-tert-butyl acrylamide, sodium sulfo-sec-butyl acrylamide, and sodium sulfo-tert-butyl methacrylamide; sulfoalkyl (meth) acrylates such as sodium sulfomethacrylamide, sodium sulfo-tert-butyl acrylamide, sodium sulfo-sec-butyl acrylamide, and sodium sulfo-tert-butyl methacrylamide; and one or more unsaturated monomers selected from these can be used.

[0061] Examples of the phosphoric acid group-containing unsaturated monomer include phosphonocarboxylic acid compounds and alkali metal salts thereof.

[0062] Examples of the vinyl ester monomers copolymerizable with the unsaturated monomers include vinyl formate, vinyl acetate, vinyl trifluoroacetate, vinyl propionate, vinyl butyrate, vinyl caprate, vinyl laurate, vinyl versatate, vinyl palmitate, vinyl stearate, etc. These may be used alone or in combination of two or more, but vinyl acetate is practically suitable.

[0063] As the polymerization method, any known polymerization method such as solution polymerization, emulsion polymerization, and suspension polymerization can be used. However, the polymerization is usually carried out by solution polymerization using an alcohol such as methanol, ethanol, or isopropanol as a solvent.

[0064] As the polymerization catalyst, according to the polymerization method, azo catalysts such as azobisisobutyronitrile, peroxide catalysts such as acetyl peroxide, benzoyl peroxide, lauroyl peroxide, etc., known polymerization catalysts can be appropriately selected, and they can be used alone or in combination of two or more. In addition, the reaction temperature is selected from the range of about 35° C. to the boiling point of the solvent.

[0065] Saponification can also be carried out by a known method. Usually, the obtained polymer is dissolved in alcohol and carried out in the presence of a saponification catalyst. As alcohol, methanol, ethanol, butanol, etc. can be mentioned. They can be used alone or in combination of two or more. From the aspect of solubility, the concentration of the copolymer in the alcohol is selected from the range of 20 to 50 mass%.

[0066] As the saponification catalyst, for example, a base catalyst such as a hydroxide or alkoxide of an alkali metal such as sodium hydroxide, potassium hydroxide, sodium methoxide, sodium ethoxide, potassium methoxide, etc. can be used, or an acid catalyst can be used. These can be used alone or in combination of two or more. The amount of the saponification catalyst used is preferably 1 to 100 millimole equivalents relative to the vinyl ester compound.

[0067] The modification amount of the anionic group-modified PVA resin used in the present invention is preferably 1 to 15 mol%, more preferably 2 to 10 mol%, particularly preferably 2 to 8 mol%, and particularly preferably 3 to 7 mol%. If the modification amount is too small, the solubility in water tends to decrease, and if it is too large, the productivity of the PVA resin tends to decrease, or the biodegradability tends to decrease, and there is a tendency to become easy to cause blocking, and the practicality becomes reduced.

[0068] The viscosity of a 4% by mass aqueous solution of the anionic group-modified PVA-based resin used in the present invention at 20°C is preferably 5 to 50 mPa·s, more preferably 13 to 40 mPa·s, and particularly preferably 17 to 30 mPa·s. If the above viscosity is too low, the mechanical strength of the water-soluble film tends to decrease, while if it is too high, the viscosity of the aqueous solution during film formation becomes high, tending to reduce productivity.

[0069] The average saponification degree of the anionic group-modified PVA resin used in the present invention is preferably 80 mol% or more, particularly preferably 85 to 99.9 mol%, further preferably 88 to 99 mol%, and particularly preferably 90 to 98 mol%. If the saponification degree is too high, the solubility in water tends to decrease, and if it is too low, the solubility of the water-soluble film in water tends to decrease over time depending on the drug to be packaged.

[0070] In the present invention, the above-mentioned hydrophilic group-modified PVA-based resins may be used alone, or two or more types different in saponification degree, viscosity, modified substance, modification amount, etc. may be used in combination.

[0071] In the present invention, from the viewpoint of compatibility with pullulan, it is preferred that an anionic group-modified PVA-based resin is contained as the hydrophilic group-modified PVA-based resin.

[0072] In particular, in terms of the balance between compatibility and water solubility and ease of handling, it is preferred to use a carboxyl group-modified PVA-based resin or a sulfonic acid group-modified PVA-based resin, and it is particularly preferred to use a carboxyl group-modified PVA.

[0073] The average saponification degree of the hydrophilic group-modified PVA resin of the present invention is preferably 80 mol% or more, particularly preferably 82 to 99.9 mol%, further preferably 85 to 99 mol%, and particularly preferably 90 to 98 mol%. If the average saponification degree is too low, the solubility of the film in water tends to decrease, or the solubility of the film tends to decrease over time depending on the drug to be packaged. It should be noted that even if the average saponification degree is too high, the solubility in water tends to decrease.

[0074] The viscosity of a 4% by mass aqueous solution of the hydrophilic group-modified PVA-based resin used in the present invention at 20° C. is preferably 5 to 60 mPa·s, particularly preferably 10 to 45 mPa·s, and further preferably 15 to 40 mPa·s. If the above viscosity is too low, the mechanical strength of the water-soluble film tends to decrease, and if it is too high, the viscosity of the aqueous solution during film formation becomes high, tending to reduce productivity.

[0075] The content of the hydrophilic group-modified PVA resin is preferably 10 to 90% by mass of the water-soluble film, more preferably 20 to 80% by mass, and further preferably 30 to 70% by mass. If the content of the hydrophilic group-modified PVA resin is within the above range, the mechanical properties of the film, especially the elongation of the film, tend to be excellent.

[0076] The content ratio of pullulan to the hydrophilic group-modified PVA resin is preferably pullulan / hydrophilic group-modified PVA resin = 1 / 99 to 99 / 1, particularly preferably 5 / 95 to 80 / 20, further preferably 10 / 90 to 60 / 40, and particularly preferably 15 / 85 to 45 / 55 in terms of mass ratio.

[0077] If the pullulan content is too high, the compatibility with the hydrophilic group-modified PVA resin tends to deteriorate, and there is a concern that the solubility of the film in water may decrease. In addition, there is a tendency for the mechanical properties such as film strength to decrease.

[0078] The water-soluble film of the present invention may use PVA resins other than the above-mentioned hydrophilic group-modified PVA resins within the scope not hindering the purpose of the invention. For example, from the perspective of adjusting the film properties such as sealing and viscoelasticity, unmodified PVA may also be used in combination.

[0079] When unmodified PVA is used together, the content ratio by mass ratio is preferably hydrophilic group-modified PVA resin / unmodified PVA = 97 / 3 to 50 / 50, more preferably 95 / 5 to 70 / 30, and particularly preferably 93 / 7 to 85 / 15. If the above content ratio is too large, the compatibility between the PVA resin and pullulan tends to decrease.

[0080] <Plasticizer>

[0081] In the present invention, from the aspect of imparting appropriate softness to the film, it is preferred to use a plasticizer in addition to pullulan and the hydrophilic group-modified PVA-based resin. The plasticizer may be used alone or in combination of two or more, but from the aspect of the mechanical properties and formability of the film, it is also preferred to use two or more.

[0082] As the above-mentioned plasticizer, for example, glycerols such as glycerol, diglycerol, and triglycerol, alkylene glycols such as diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, and dipropylene glycol, trimethylolpropane, sorbitol, xylitol, and maltitol, etc. can be enumerated. These can be used alone or in combination of two or more. Among them, glycerol, diglycerol, and polyethylene glycol are preferred from the aspect of easy acquisition and the plasticizing effect can be obtained in a small amount. In addition, sorbitol is preferably used in terms of the stability of the package over time.

[0083] The content of the plasticizer is preferably 5 to 60 parts by mass, more preferably 10 to 55 parts by mass, particularly preferably 15 to 55 parts by mass, further preferably 18 to 50 parts by mass, or 20 to 45 parts by mass relative to a total of 100 parts by mass of pullulan and the hydrophilic group-modified PVA-based resin. If the content of the above-mentioned plasticizer is too little, there is a tendency that the plasticizing effect is low, the processability is reduced, or the toughness of the water-soluble film is destroyed over time when the package is formed. If it is too much, there is a tendency that the strength of the film is reduced or it becomes easy to produce adhesion.

[0084] <Packing>

[0085] In the present invention, a filler may be further contained as necessary.

[0086] The filler is contained for the purpose of improving anti-blocking property. Such filler is not particularly limited, and any of organic fillers and inorganic fillers can be used, and organic fillers are particularly suitable. They can be used alone or in combination of two or more. The average particle size of the filler is preferably 0.1 to 50 μm, and particularly preferably 1 to 35 μm.

[0087] The average particle size of the filler is a value measured by a laser diffraction particle size distribution analyzer and is calculated from the D50 value (particle size at cumulative 50%) of the obtained cumulative volume distribution.

[0088] The organic filler refers to a particulate substance (primary particle) composed of an organic compound and having any shape such as needle-like, rod-like, layer-like, scale-like, or spherical, or an aggregate of the particulate substance (secondary particle).

[0089] As the above-mentioned organic filler, it is mainly selected from polymer compounds, for example, in addition to melamine resins, poly(methyl)acrylate resins, polystyrene resins, biodegradable resins such as starch and polylactic acid, etc. can also be mentioned. Among them, biodegradable resins such as poly(methyl)acrylate resins, polystyrene resins, and starch are preferred, and starch is particularly preferred from the perspective of the dispersibility of the hydrophilic group-modified PVA resin.

[0090] Examples of the starch include raw starch (corn starch, potato starch, sweet potato starch, wheat starch, cassava starch, sago starch, tapioca starch, sorghum starch, rice starch, bean starch, kudzu starch, fern starch, lotus root starch, water chestnut starch, etc.), physically modified starch (α-starch, separated amylose, moisture-heat treated starch, etc.), enzyme-modified starch (hydrolyzed dextrin, enzymatically decomposed dextrin, amylose, etc.), chemically decomposed modified starch (acid-treated starch, hypochlorous acid oxidized starch, dialdehyde starch, etc.), chemically modified starch derivatives (esterified starch, etherified starch, cationized starch, cross-linked starch, etc.), etc. Among them, unprocessed starch, particularly corn starch and rice starch, are preferably used from the perspective of easy availability and economic efficiency.

[0091] The mass ratio of the starch to pullulan when used is preferably 2 to 60 parts by mass, more preferably 10 to 50 parts by mass, and still more preferably 20 to 40 parts by mass relative to 100 parts by mass of pullulan. If the above content is too low, there is a tendency for adhesion, and if it is too high, there is a tendency for the sealing property of the film to be reduced or the formability when made into a package to be reduced.

[0092] The average particle size of the organic filler is preferably 2 to 50 μm, more preferably 4 to 45 μm, particularly preferably 10 to 40 μm, and further preferably 15 to 35 μm. If the average particle size is too small, the blocking property of the film tends to increase, while if it is too large, the fillers tend to aggregate with each other, the dispersibility decreases, or pinholes tend to form when the film is stretched during molding.

[0093] The inorganic filler refers to a granular substance (primary particle) composed of an inorganic compound and having any shape such as needle-like, rod-like, layer-like, scale-like, or spherical, or an aggregate of the granular substance (secondary particle).

[0094] Examples of the inorganic filler include oxide-based inorganic compounds such as silica, diatomaceous earth, titanium oxide, calcium oxide, magnesium oxide, aluminum oxide, barium oxide, germanium oxide, tin oxide, and zinc oxide, talc, clay, kaolin, mica, asbestos, gypsum, graphite, glass balloons, glass beads, calcium sulfate, barium sulfate, ammonium sulfate, calcium sulfite, calcium carbonate, whisker-shaped calcium carbonate, magnesium carbonate, dawsonite, dolomite, potassium titanate, carbon black, glass fiber, aluminum oxide fiber, boron fiber, processed mineral fiber, carbon fiber, carbon hollow sphere, bentonite, montmorillonite, copper powder, sodium sulfate, potassium sulfate, zinc sulfate, copper sulfate, iron sulfate, magnesium sulfate, aluminum sulfate, potassium aluminum sulfate, ammonium nitrate, sodium nitrate, potassium nitrate, aluminum nitrate, ammonium chloride, sodium chloride, potassium chloride, magnesium chloride, calcium chloride, sodium phosphate, potassium chromate, etc. These may be used alone or in combination of two or more.

[0095] Among them, oxide-based inorganic compounds and talc are preferably used, titanium oxide, talc, and silicon dioxide are particularly preferably used, and silicon dioxide is further preferably used.

[0096] The average particle size of the inorganic filler is preferably 1 to 20 μm, particularly preferably 2 to 15 μm, and further preferably 3 to 10 μm. If the average particle size is too small, the flexibility and toughness of the film tend to decrease, or the blocking property tends to increase. If the average particle size is too large, pinholes tend to be formed when the film is stretched during molding.

[0097] The content of the filler is preferably 1 to 30 parts by mass, particularly preferably 1.5 to 25 parts by mass, and further preferably 2 to 20 parts by mass relative to 100 parts by mass of the total of pullulan and the hydrophilic group-modified PVA-based resin. If the above content ratio is too small, the stickiness of the film tends to increase, and if it is too large, the softness and toughness of the film tend to decrease.

[0098] <Surfactant>

[0099] In the present invention, a surfactant or the like may be further contained as necessary.

[0100] The surfactant used in the present invention is contained for the purpose of improving the releasability from the casting surface during film production, and generally includes nonionic surfactants, cationic surfactants, and anionic surfactants.

[0101] As such a surfactant, for example, polyoxyethylene nonylphenyl ether, polyoxyethylene octyl nonyl ether, polyoxyethylene dodecyl phenyl ether, polyoxyethylene alkyl allyl ether, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene alkyl amino ethers such as polyoxyethylene alkyl ether phosphate monoethanolamine salt, polyoxyethylene lauryl amino ether, polyoxyethylene stearyl amino ether, sorbitan monopalmitate, sorbitan monostearate, stearic acid glyceryl, sucrose fatty acid ester, etc. can be enumerated, and they can be used alone or in combination of two or more. Among them, in terms of manufacturing stability, polyoxyethylene alkyl ether phosphate monoethanolamine salt and polyoxyethylene lauryl amino ether are suitable. These surfactants can be used alone or in combination of two or more.

[0102] The content of the surfactant is preferably 0.01 to 3 parts by mass, particularly preferably 0.05 to 2.5 parts by mass, and further preferably 0.1 to 2 parts by mass relative to 100 parts by mass of the total of pullulan and the hydrophilic group-modified PVA-based resin. If the content is too small, the peelability between the casting surface of the film-making device and the film after film-making is reduced, and the productivity tends to be reduced. If the content is too large, it tends to become easy to stick, or the bonding strength when the film is used to form a package body tends to be reduced.

[0103] <Other ingredients>

[0104] It should be noted that, as other components, other water-soluble polymers other than the hydrophilic group-modified PVA-based resin (for example, sodium polyacrylate, polyethylene oxide, polyvinyl pyrrolidone, dextrin, chitosan, chitin, methyl cellulose, hydroxyethyl cellulose, etc.), fragrances, rust inhibitors, colorants, extenders, defoamers, ultraviolet absorbers, liquid paraffins, fluorescent whitening agents, bitter ingredients (for example, denatonium benzoate, etc.), etc. may be contained within the scope of not hindering the purpose of the invention. These may be used alone or in combination of two or more.

[0105] The content of the above-mentioned other components is preferably less than 5 mass parts, particularly preferably less than 1 mass part, and further preferably less than 0.5 mass part relative to 100 mass parts of hydrophilic group-modified PVA-based resins. The lower limit is usually 0 mass part. If the above-mentioned content is too much, there is a tendency that the compatibility with pullulan is reduced and the durability is reduced.

[0106] In addition, in the present invention, an antioxidant may be blended. Examples of the antioxidant include sulfites such as sodium sulfite, potassium sulfite, calcium sulfite, and ammonium sulfite, tartaric acid, ascorbic acid, sodium thiosulfate, catechol, and Rongalite. Among them, sulfites are preferred, and sodium sulfite is particularly preferred. The blending amount is preferably 0.1 to 10 parts by mass, particularly preferably 0.2 to 5 parts by mass, and further preferably 0.3 to 3 parts by mass relative to 100 parts by mass of the hydrophilic group-modified PVA-based resin.

[0107] <<Manufacturing of water-soluble films>>

[0108] In the present invention, pullulan, a hydrophilic group-modified PVA-based resin, preferably a plasticizer, and other components such as fillers and surfactants as needed are blended as described above, dissolved or dispersed in water to prepare a film-forming raw material, which is then formed into a film.

[0109] <Dissolving process>

[0110] In the dissolving step, the components blended above are dissolved or dispersed in water to prepare an aqueous solution or aqueous dispersion as a membrane-forming raw material.

[0111] When preparing the film-forming raw materials, the mixing method of pullulan, hydrophilic group-modified PVA-based resin, and other additives is not particularly limited. For example, the following methods can be cited: a method of mixing pullulan, hydrophilic group-modified PVA-based resin and other additives to form a mixture, mixing the mixture with water, and dissolving it; a method of dissolving pullulan, hydrophilic group-modified PVA-based resin and other additives independently in water and then mixing them; a method of dissolving pullulan and hydrophilic group-modified PVA-based resin independently in water and then mixing and dissolving them with other additives; etc.

[0112] As a dissolution method when dissolving in water, room temperature dissolution, high temperature dissolution, pressure dissolution, etc. are generally used. Among them, high temperature dissolution and pressure dissolution are preferred from the viewpoint of less undissolved matter and excellent productivity.

[0113] The dissolution temperature is usually 80 to 100°C, preferably 90 to 100°C in the case of high temperature dissolution, and is usually 80 to 130°C, preferably 90 to 120°C in the case of pressure dissolution.

[0114] The dissolution time is usually 1 to 20 hours, preferably 2 to 15 hours, and more preferably 3 to 10 hours. If the dissolution time is too short, undissolved matter tends to remain, while if it is too long, productivity tends to decrease.

[0115] Furthermore, after the dissolution, the obtained film-forming raw material is subjected to a degassing treatment, and examples of the degassing method include static degassing, vacuum degassing, twin-screw extrusion degassing, etc. Among them, static degassing and twin-screw extrusion degassing are preferred.

[0116] The degassing temperature is usually 50 to 100° C., preferably 60 to 95° C., and particularly preferably 65 to 80° C. If the degassing temperature is too high, the molecular chain of pullulan is cut and the viscosity of the film-forming raw material tends to decrease, while if it is too low, the viscosity becomes high, degassing takes time, and productivity tends to decrease.

[0117] The degassing time is usually 2 to 30 hours, preferably 5 to 25 hours.

[0118] The solid content concentration of the film-forming raw material is preferably 10 to 60% by mass, particularly preferably 12 to 50% by mass, and further preferably 15 to 40% by mass. If the concentration is too low, the productivity of the film tends to decrease, and if it is too high, the viscosity becomes too high, the degassing of the film-forming raw material takes time, and a parting line tends to be generated during film formation.

[0119] The pH of the membrane-forming raw material is usually 4 to 8, preferably 4.8 to 7.5.

[0120] <Film-making process>

[0121] In the film forming step, the film forming raw material prepared in the dissolving step is formed into a film shape and, if necessary, dried to prepare a water-soluble film having a water content of less than 15% by mass.

[0122] As the film forming method, for example, a melt extrusion method, a casting method or the like can be adopted, and the casting method is preferred in terms of the accuracy of the film thickness.

[0123] When the casting method is carried out, for example, the above-mentioned film-making raw material is discharged from the slit of a T-shaped slit die, etc., and cast onto a casting surface such as the surface of a plastic substrate such as a polyethylene terephthalate film, such as the metal surface of an endless belt or a drum roll, and then dried and further heat-treated as needed, thereby producing a water-soluble film.

[0124] The water-soluble film peeled off from the casting surface such as the surface of the plastic substrate in the film-forming process is transported and wound on a core tube to obtain a film roll. The obtained film roll can be supplied directly as a product, or preferably, it can be supplied in the form of a film roll obtained by slitting the water-soluble film into a film width of a desired size.

[0125] The surface of the water-soluble film can be flat, but from the perspective of anti-blocking, slippage during processing, reduced adhesion between products, and appearance, it is also preferred to pre-implant embossing patterns, fine concave-convex patterns, special engraved patterns, etc. on one or both sides of the film.

[0126] The thickness of the water-soluble film is appropriately selected according to the application, etc., and is preferably 10 to 120 μm, particularly preferably 15 to 110 μm, and further preferably 20 to 100 μm. If the thickness is too thin, the mechanical strength of the film tends to decrease, and if it is too thick, the dissolution rate in water tends to slow down, and the film-forming efficiency tends to decrease.

[0127] The width of the water-soluble film is appropriately selected according to the application, and is preferably 300 to 5000 mm, particularly preferably 500 to 4000 mm, and further preferably 600 to 3000 mm. If the width is too narrow, productivity tends to decrease, while if it is too wide, control of sag and film thickness tends to become difficult.

[0128] The length of the water-soluble film is appropriately selected according to the application, and is preferably 100 to 20,000 m, particularly preferably 800 to 15,000 m, and further preferably 1,000 to 10,000 m. If the length is too short, the switching of the film requires time, thereby reducing productivity, and if it is too long, there is a tendency to produce poor appearance due to tight winding.

[0129] In addition, the water content of the obtained water-soluble film is preferably 3 to 15% by mass, particularly preferably 5 to 9% by mass, and further preferably 6 to 8% by mass in terms of mechanical strength and heat sealability. If the water content is too low, the film tends to become too hard and the formability and impact resistance of the package body when made into a package body tend to decrease. If it is too high, there is a tendency to become easy to cause blocking. When adjusting the water content, it can be achieved by appropriately setting the drying conditions and the humidity control conditions.

[0130] In addition, the said water content is measured based on JIS K 67263.4, and the value of the volatile matter obtained is made into the water content.

[0131] The water-soluble film of the present invention may be used as a single layer or in the form of a multilayer structure in which other films or resin layers are laminated.

[0132] The water-soluble film of the present invention thus obtained is particularly useful in packaging (unit packaging) of pesticides, detergents and other drugs, and in edible applications (food packaging). The food packaged with the film may be in the form of granules, tablets, powders, etc., and is preferably a dry food such as food ingredients and ingredients such as instant food.

[0133] <<Pharmaceutical packaging>>

[0134] The medicine package body as one embodiment of the present invention is formed by covering the medicine with a packaging body containing the obtained water-soluble film. Since the medicine is packaged with the packaging body containing the water-soluble film, when the medicine is put into water together with the packaging body, the packaging body (water-soluble film) on the surface dissolves and the medicine is exposed, and it dissolves or disperses in water, and the effect of the medicine can be manifested. Therefore, the medicine package body as one embodiment of the present invention is suitable as a medicine package body for encapsulating a relatively small amount of medicine such as a single dose.

[0135] As the above-mentioned agent, for example, pesticides such as insecticides, fungicides, herbicides, fertilizers, detergents, etc. can be cited, and detergents such as washing detergents and dishwashing detergents are particularly preferred. Such agents can be liquid or solid, and the shape of the solid can be, for example, granules, tablets, powders, etc. The agent is preferably a drug that is dissolved or dispersed in water, and encapsulated liquid detergents are particularly preferred. The pH of such agents can be alkaline, neutral, or acidic.

[0136] The pH value of the liquid detergent when dissolved or dispersed in water is preferably 6 to 12, particularly preferably 7 to 11. In addition, the water content of the liquid detergent is preferably 15% by mass or less, particularly preferably 0.1 to 10% by mass, and further preferably 0.1 to 7% by mass. When the water content of the liquid detergent is within the above range, the water solubility is excellent and the water-soluble film tends not to gel or insolubilize.

[0137] The pH value is measured in accordance with JIS K 3362 8.3. The water content is measured in accordance with JIS K 3362 7.21.3.

[0138] <<Manufacturing of pharmaceutical packaging>>

[0139] When a medicine such as a liquid detergent is packaged to form a medicine package using the water-soluble film of the present invention, a known method can be adopted.

[0140] For example, the drug can be placed between two opposing water-soluble films (a first water-soluble film and a second water-soluble film), and the overlapping portions (contact portions) of the water-soluble films around the drug are pressed and bonded together to produce the drug.

[0141] Specifically, a lower mold of the molding device is prepared with a recess having a shape in which a drug can be placed, and a first water-soluble film (bottom film) is fixed to the lower mold to mold the bottom film into a shape along the lower mold.

[0142] On the other hand, the second water-soluble film (top film) is also fixed to the upper mold of the molding device. Then, after placing (putting) a separately prepared liquid detergent or other medicine in the molded bottom film, the upper mold and the lower mold are pressed tightly, so that the top film around the medicine abuts against the bottom film, and the abutting portion is pressed under vacuum. After the pressing, the vacuum is released, thereby obtaining a medicine packaging body in which the medicine is enclosed in the water-soluble film.

[0143] Examples of the method for pressure-bonding the film include heat sealing, water sealing, and glue sealing. Among them, water sealing is preferably used because pressure-bonding conditions and the like can be easily controlled.

[0144] Example

[0145] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the following Examples unless the gist of the invention is exceeded.

[0146] It should be noted that, in the examples, "parts" refer to mass standards.

[0147] As material components of the water-soluble film, the following components were prepared.

[0148] (PVA resin)

[0149] · Hydrophilic group modified PVA resin.

[0150] (1) Carboxyl-modified PVA-based resin: 4% aqueous solution viscosity at 20° C. 22 mPa·s, average saponification degree 94 mol %, modification amount based on monomethyl maleate 2.0 mol %.

[0151] (2) Sulfonic acid group-modified PVA-based resin: 4% aqueous solution viscosity at 20° C. 2.5 mPa·s, average saponification degree 88 mol %, modification amount based on sodium allyl sulfonate 2.5 mol %.

[0152] (3) Sulfonic acid group-modified PVA-based resin: 4% aqueous solution viscosity at 20° C. 2.8 mPa·s, average saponification degree 99 mol % or more, modification amount based on sodium allyl sulfonate 2.5 mol %.

[0153] Unmodified PVA.

[0154] (4) Unmodified PVA: 4% aqueous solution viscosity at 20°C 18 mPa·s, average saponification degree 88 mol %.

[0155] (Pullulan)

[0156] ·Pulululan (manufactured by Hayashihara Co., Ltd.)

[0157] (Plasticizer)

[0158] ·glycerin

[0159] ·Sorbitol

[0160] (filler)

[0161] Starch (corn starch, average particle size 20 μm)

[0162] [Example 1]

[0163] Preparation of water-soluble films

[0164] A 10% aqueous solution of a carboxyl-modified PVA resin (1) and a 10% aqueous solution of pullulan were mixed so that the carboxyl-modified PVA resin was 80 parts and the pullulan was 20 parts, and 15 parts of glycerol were further mixed to obtain a film-forming raw material as an aqueous dispersion of a resin composition having a solid content concentration of 10%. The obtained film-forming raw material was left to stand at room temperature to degas.

[0165] The film-forming raw material after standing and degassing was poured into a 10 cm×10 cm frame formed on a polyester film and stood in an environment of 23° C.×50% RH to dry to obtain a water-soluble film with a thickness of 100 μm. The water content of the water-soluble film was 7.5% by mass.

[0166] [Example 2]

[0167] In Example 1, except that the contents of the carboxyl-modified PVA-based resin (1) and pullulan were changed to the amounts shown in Table 1 described later, a water-soluble film was prepared in the same manner and evaluated in the same manner.

[0168] [Example 3]

[0169] In Example 1, the contents of the carboxyl-modified PVA-based resin (1) and pullulan were changed to the amounts shown in Table 1 described below, and the types of additional plasticizers and fillers were changed to the contents shown in Table 1 described below. Except for this, a water-soluble film was prepared in the same manner and evaluated in the same manner.

[0170] [Example 4]

[0171] In Example 1, except that the contents of the carboxyl-modified PVA-based resin (1) and pullulan were changed to the amounts shown in Table 1 described later, a water-soluble film was prepared in the same manner and evaluated in the same manner.

[0172] [Example 5]

[0173] In Example 1, a water-soluble film was prepared in the same manner and evaluated in the same manner except that a carboxyl-modified PVA-based resin (1) and an unmodified PVA-based resin (4) were used as PVA-based resins in the amounts shown in Table 1 described later.

[0174] [Example 6]

[0175] In Example 5, a water-soluble film was prepared in the same manner and evaluated in the same manner except that the amounts of the carboxyl-modified PVA-based resin (1) and the unmodified PVA-based resin (4) were changed to those shown in Table 1 described later.

[0176] [Example 7]

[0177] In Example 4, a water-soluble film was prepared in the same manner, and evaluated in the same manner, except that the sulfonic acid group-modified PVA-based resin (2) was used as the PVA-based resin.

[0178] [Example 8]

[0179] In Example 4, a water-soluble film was prepared in the same manner, and evaluated in the same manner, except that the sulfonic acid group-modified PVA-based resin (3) was used as the PVA-based resin.

[0180] [Comparative Example 1]

[0181] In Example 1, except that the unmodified PVA-based resin (4) was used as the PVA-based resin, a water-soluble film was prepared in the same manner and evaluated in the same manner.

[0182] It should be noted that the prepared membrane-forming raw materials had poor compatibility and slightly phase-separated.

[0183] [Comparative Example 2]

[0184] In Comparative Example 1, a water-soluble film was prepared in the same manner, and evaluated in the same manner, except that the contents of the unmodified PVA-based resin (4) and pullulan were changed to the amounts shown in Table 1 described later.

[0185] It should be noted that the prepared membrane-forming raw materials had poor compatibility and phase separation occurred.

[0186] Using these obtained water-soluble films, the compatibility, solubility, and mechanical properties were evaluated based on the methods and criteria shown below. The results are shown in Table 1 below.

[0187] <Compatibility>

[0188] [Evaluation method]

[0189] The presence or absence of the sea-island structure of the water-soluble film was visually observed and evaluated based on the following criteria.

[0190] [Evaluation criteria]

[0191] ○(very good)…There are few sea-island structures, almost no phase separation, and it is transparent.

[0192] ×(poor)…The islands in the sea-island structure are large and phase separation has obviously occurred.

[0193] <Solubility>

[0194] [Evaluation method]

[0195] The water-soluble film obtained above was cut into a size of 3.5 cm × 3.5 cm, placed in a 1-liter beaker filled with water (1 liter) and fixed with a jig, and stirred with a stirrer (rotor length 3 cm, rotation speed 750 rpm) while the water temperature was maintained at 20°C. The situation where no dispersion of insoluble particles with a diameter of more than 1 mm was observed in the above film was recorded as dissolved, and the time required for dissolution was evaluated based on the following criteria.

[0196] [Evaluation criteria]

[0197] ○(very good)…dissolves in less than 120 seconds.

[0198] △(good)…Dissolves within 120 to 300 seconds.

[0199] ×(poor) ... did not dissolve even after more than 300 seconds.

[0200] <Mechanical properties>

[0201] [Evaluation method]

[0202] The water-soluble film obtained above was used to measure the "tensile strength" and "tensile elongation" according to JIS K 7127 (1999). That is, after being left to stand for 24 hours under 23°C and 50%RH humidity conditions before measurement, the water-soluble film was measured for tensile strength and tensile elongation at a tensile speed of 200 mm / min using AUTOGRAPHAG-X Plus (manufactured by Shimadzu Corporation) under this environment (film width 15 mm, chuck spacing 50 mm). These measured values ​​were evaluated based on the following criteria.

[0203] [Evaluation criteria]

[0204] ◎(excellent) ... The tensile strength is 10 MPa or more and the tensile elongation exceeds 300%.

[0205] 0 (very good) ... The tensile strength is 10 MPa or more and the tensile elongation is 200 to 300%, or the tensile strength is 5 MPa or more and less than 10 MPa and the tensile elongation exceeds 300%.

[0206] △ (good) ... The tensile strength is 5 MPa or more and less than 10 MPa, and the tensile elongation is 200 to 300%.

[0207] × (poor) ... the tensile strength is 0 to less than 5 MPa and / or the tensile elongation is less than 200%.

[0208] Furthermore, using the water-soluble films of Examples 1, 4, 5, 7, and 8, packaging bodies were produced by the method described below, and the moldability was evaluated.

[0209] Furthermore, for the water-soluble films of Examples 1 and 5, packaging bodies having a plurality of partitions were produced, and the moldability and compressive strength were evaluated based on the methods and criteria described below.

[0210] These results are shown in Table 2 described later.

[0211] Packaging production

[0212] The water-soluble film obtained above was used to produce a packaging body by the following procedure using a packaging body manufacturing machine manufactured by Engel.

[0213] That is, after the water-soluble film was left to stand for 24 hours and humidified under the humidity-adjusting conditions of 23° C. and 40% RH, the first water-soluble film (bottom film) was fixed on a mold (A) having a concave portion located at the lower part of the device (molded package: 45 mm in length, 42 mm in width, and 30 mm in height) under this environment, and the second water-soluble film (top film) was also fixed on the upper part of the device in a state where it was opposed to the bottom film. The bottom film was heated for 4 seconds in a dryer generating hot air at 100° C., and the bottom film was vacuum-formed in a shape along the mold.

[0214] Then, 34 mL of a commercially available liquid laundry detergent (composition summary: 11% propylene glycol, 7.5% glycerin, 67% surfactant, 14.2% water, pH 7.5) was injected into the concave portion of the formed bottom film. 0.25 g of water was applied to the entire surface of the top film (80 mm in length and 140 mm in width), and the top film and the bottom film were pressed together. After 10 seconds of pressing, the vacuum was released to produce a package (A).

[0215] In addition, using a mold (B) having a concave portion divided into three sections (molded package: 45 mm in length, 45 mm in width, 20 mm in height), an empty package (B) containing no detergent was produced under the same conditions as above.

[0216] <Moldability>

[0217] In the production of the package, the followability of the base film to the mold during vacuum forming was visually confirmed and evaluated based on the following criteria. At this time, the evaluation when producing the package (A) was referred to as "formability (A)", and the evaluation when producing the package (B) was referred to as "formability (B)".

[0218] [Evaluation criteria]

[0219] ○ (very good) ... The film follows the mold well in less than 30 seconds.

[0220] △ (good) ... A slight gap was visible between the film and the mold, or it took more than 30 seconds until the film fully followed the mold.

[0221] ×(poor)…The film obviously floats off the mold and does not follow it.

[0222] <Compression strength>

[0223] In the production of the above-mentioned packaging body, the liquid detergent packaging body obtained using the mold (A) was measured for compressive strength by the method shown below, and evaluated based on the following criteria.

[0224] [Evaluation method]

[0225] The liquid detergent package produced by the above method was left to stand for 1 hour in an environment of 23°C and 40% RH, and then the compressive strength of the liquid detergent package when broken was measured under the same environment using AUTOGRAPH AG-X Plus (manufactured by Shimadzu Corporation) at a test speed of 200 mm / min. It should be noted that the load cell used was 5 kN.

[0226] [Evaluation criteria]

[0227] ○(very good)…Compression strength exceeds 1000N.

[0228] △ (good) ... compression strength is 300 or more and 1000N or less.

[0229] ×(poor) ... When the compression strength is less than 300N, the bag is easily broken, or the sealing surface is easily peeled off, thereby breaking the bag.

[0230] [Table 1]

[0231]

[0232] [Table 2]

[0233]

[0234] According to the results of the examples, the pullulan of the water-soluble film of the present invention containing pullulan and the modified PVA-based resin modified with a hydrophilic group has good compatibility with the PVA-based resin, and a transparent film with excellent appearance is obtained, and the water solubility is also excellent. In addition, it is known that the mechanical properties are also excellent, and when the film is used to make a packaging body, it has excellent formability, and therefore, it is suitable for practical use as an independent packaging purpose.

[0235] Furthermore, it was found that the water-soluble film of the present invention has excellent moldability even in a complex shape, shows sufficient strength in the evaluation of compressive strength, is easily peeled off at the sealed surface without breaking the bag, and is also excellent in water sealing properties.

[0236] On the other hand, it can be seen that in the comparative example using unmodified PVA resin as PVA resin, the compatibility with pullulan is poor, and a uniform film-making raw material cannot be obtained. Therefore, the non-compatible part becomes a disadvantage during film-making, or a problem occurs during film winding, and the film-making property is poor, and the transparency appearance of the obtained film is also poor. In addition, it can be seen that the solubility is also poor, and it is not suitable for practical use as an independent packaging purpose.

[0237] The above embodiments show specific aspects of the present invention, but the above embodiments are merely examples and are not to be construed as limiting. Various modifications that are obvious to those skilled in the art are within the scope of the present invention.

[0238] Industrial Applicability

[0239] The water-soluble film of the present invention can be used for packaging (unit packaging) of pesticides, detergents and other chemicals, (hydraulic) transfer films, sanitary napkins / diapers and other physiological products, ostomy bags and other waste disposal products, medical products such as blood-absorbing sheets, temporary substrates such as seedling sheets / seed tapes / embroidery base fabrics, etc.

[0240] The film of the present invention, which is a mixed film of a PVA-based resin used also in foods and pharmaceuticals and a natural raw material, is also useful in edible applications (food packaging).

Claims

1. A water-soluble film, characterized in that: Contains pullulan and a modified polyvinyl alcohol-based resin modified with a hydrophilic group.

2. The water-soluble film according to claim 1, characterized in that: The modified polyvinyl alcohol-based resin modified with a hydrophilic group is an anionic group-modified polyvinyl alcohol-based resin.

3. The water-soluble film according to claim 1 or 2, characterized in that: The content ratio of the pullulan to the modified polyvinyl alcohol-based resin modified with a hydrophilic group is 1 / 99 to 99 / 1 in terms of mass ratio.

4. The water-soluble film according to any one of claims 1 to 3, characterized in that Also contains plasticizers.

5. The water-soluble film according to claim 4, characterized in that: The pullulan and the modified polyvinyl alcohol resin modified with a hydrophilic group have a content ratio of 5 / 95 to 80 / 20 in terms of mass ratio, and the plasticizer content is 5 to 60 parts by mass based on 100 parts by mass of the total of the pullulan and the modified polyvinyl alcohol resin modified with a hydrophilic group.

6. The water-soluble film according to any one of claims 1 to 5, characterized in that Also contains fillers.

7. The water-soluble film according to claim 6, characterized in that: The filler is starch.

8. The water-soluble film according to claim 7, characterized in that: The starch is contained in an amount of 2 to 60 parts by mass based on 100 parts by mass of the pullulan.

9. The water-soluble film according to any one of claims 6 to 8, characterized in that The modified polyvinyl alcohol resin modified with a hydrophilic group is an anionic group-modified polyvinyl alcohol resin. The content ratio of the pullulan to the anionic group-modified polyvinyl alcohol-based resin is 5 / 95 to 80 / 20 in terms of mass ratio.

10. The water-soluble film according to any one of claims 1 to 9, characterized in that The water content is 3 to 15% by mass.

11. The water-soluble film according to any one of claims 1 to 10, characterized in that: Used for pharmaceutical packaging.

12. The water-soluble film according to any one of claims 1 to 10, characterized in that: Used for food packaging.

13. A method for producing a water-soluble film according to any one of claims 1 to 12, characterized in that: The method comprises the following steps: a casting step of preparing a film-forming raw material containing pullulan and a modified polyvinyl alcohol-based resin modified with a hydrophilic group, and casting the film-forming raw material on a casting surface; and a drying step of drying the film-forming raw material cast on the casting surface.

14. A medicine package, comprising: A package comprising the water-soluble film according to claim 11, and a drug enclosed in the package.

15. The medicine packaging body according to claim 14, characterized in that: The agent is a liquid detergent.

16. A method for manufacturing a medicine package according to claim 14 or 15, characterized in that: The following processes are available: preparing a first water-soluble film, a second water-soluble film and a reagent; The first water-soluble film and the second water-soluble film are placed opposite to each other, and the medicine is arranged between the first water-soluble film and the second water-soluble film, so that the first water-soluble film and the second water-soluble film overlap, so that the first water-soluble film around the medicine abuts against the second water-soluble film, and the abutting portion is pressed.

Citation Information

Patent Citations

  • Water-soluble film

    JP1993001198A

  • Glucan-based film delivery system

    JP2005528328A

Cited By

  • High-temperature-resistant water-soluble polyvinyl alcohol packaging film as well as preparation method and application thereof

    CN120737523A

  • A high-temperature resistant, water-soluble polyvinyl alcohol packaging film, its preparation method and application

    CN120737523B